Principal leadership in improving teacher performance: systematic literature review - Mayasari, Evi (Universitas Islam Negeri Raden Intan Lampung, 2021)
The leadership of the head seems to greatly affect the success of the learning process in schools. One factor in the success of learning is the quality of teacher performance. This study aims to determine the principal's leadership in improving teacher performance. The method used in this study is a systematic literature review. Data collection was carried out by searching for journals with a range of 2016 to 2020 relating to teacher leadership and performance. The articles used are sourced from Garuda Research, Technology and Higher Education accredited by SINTA. The results showed that of the 329 articles related to the variables studied were 8 articles and showed that to improve teacher performance the principal's leadership applied discipline methods, providing motivation, work coaching/development, giving rewards, controlling and supervising teacher performance, and leadership. principals in improving teacher performance are using democratic leadership types, good communication and charisma. Suggestions for principals when improving teacher performance should be principals not only from competence but also by using a leadership style that prioritizes deliberation.